2017
DOI: 10.1002/jlb.3a0717-308r
|View full text |Cite
|
Sign up to set email alerts
|

Protease activated-receptor 2 is necessary for neutrophil chemorepulsion induced by trypsin, tryptase, or dipeptidyl peptidase IV

Abstract: Compared to neutrophil chemoattractants, relatively little is known about the mechanism neutrophils use to respond to chemorepellents. We previously found that the soluble extracellular protein dipeptidyl peptidase IV (DPPIV) is a neutrophil chemorepellent. In this report, we show that an inhibitor of the protease activated receptor 2 (PAR2) blocks DPPIV-induced human neutrophil chemorepulsion, and that PAR2 agonists such as trypsin, tryptase, 2f-LIGRL, SLIGKV, and AC55541 induce human neutrophil chemorepulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…, 2018). The AprA-related neutrophil chemorepellent DPPIV also uses a G protein–coupled receptor to repel cells (White et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2018). The AprA-related neutrophil chemorepellent DPPIV also uses a G protein–coupled receptor to repel cells (White et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An orthologue of AprA, dipeptidyl peptidase IV (DPPIV), acts as a chemorepellent for neutrophils (Herlihy et al. , 2013a, 2015, 2017; White et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have in fact suggested an anti-inflammatory role of PAR2 but in a cellular context-dependent manner. For example, loss of PAR2 augmented lung inflammation induced by Pseudomonas aeruginosa primarily by activating macrophages, and a low dose of a PAR2 receptor agonist reduced neutrophil influx in a mouse model of ARDS (Moraes et al, 2008; White et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Treatment with inhaled DPPIV prevented an increase in lung neutrophils in a mouse model of ARDS (Herlihy et al, 2013a), and localized injections of DPPIV decreased symptoms of arthritis in a mouse model (Herlihy et al, 2015). We then found that the DPPIV receptor is the proteaseactivated G protein-coupled receptor PAR 2, that PAR 2 agonists induce human neutrophil chemorepulsion, and when administered by aspiration into the airways, PAR 2 agonists show good efficacy at reducing the inappropriate influx of neutrophils into the lungs in a mouse model of ARDS (White et al, 2018). Together, this suggests…”
Section: Development Of Potential Therapeutics Based On Dictyosteliummentioning
confidence: 79%